Shaping Tourist Preferences and Economic Opportunities: A Case of Attraction and E-WOM at Glamping Alengkong Bali Camp - Maheswari, Anak Agung Istri Agung; Cahaya, Ni Putu Meisa; Parasari, Nyoman Sri Manik; Pradhana, I Putu Dharmawan (International Journal of Economics Development Research (IJEDR), 2025)
Bali’s tourism sector has grown rapidly, becoming a key driver of the regional economy. Among its emerging trends is glamping—a form of luxury camping that combines natural immersion with modern comfort. Alengkong Bali Camp is one such destination offering unique outdoor lodging experiences. Tourist preferences in choosing glamping accommodations are influenced by multiple factors, particularly destination attraction and electronic word of mouth (E-WOM). This study aims to examine how tourist attraction and E-WOM shape visitor preferences and indirectly contribute to the economic potential of glamping tourism. The research was conducted at Alengkong Bali Camp using a quantitative descriptive approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) with 112 respondents selected through accidental sampling. The findings reveal that both tourist attraction and E-WOM have a significant and positive effect on tourists’ decisions to stay, indicating their central role in forming visitor preferences. These preferences are critical not only for operational success but also for creating sustained economic opportunities in the local tourism ecosystem. To enhance these effects, glamping managers are encouraged to enrich nature-based activities, improve family-oriented facilities, and strategically promote online reviews to attract potential visitors.